Solanum anomalum Leaf Extract and Fractions Attenuate Oxidative Stress and Liver Injuries in Alloxan-Induced Diabetic Rats - Idongesit Charles Etuk; John Akpan Udobang; Nwakaego Omonigho Ebong; Jude Efiom Okokon (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
The leaf of Solanum anomalum used in ethnomedicine for the treatment of various ailments such as diabetes was evaluated for antioxidative stress and hepatoprotective potentials against hepatic injuries in alloxan-induced diabetic rats. Antioxidative stress and hepatoprotective activities of leaf extract and fractions (70-210 mg/kg) were assessed by determining oxidative stress markers levels, liver function indices and histopathological study of livers of treated rats. The leaf extract and fractions caused significant (p<0.05 0.001) increases in the levels of oxidative stress markers (SOD, CAT, GPx, GSH) in the livers of the treated diabetic rats. The extract/fractions treatment caused reduction in liver enzymes (ALT, AST and ALP), total and direct bilirubin. Histology of the livers revealed absence or significant reductions in pathological features in the treated diabetic rats compared to untreated diabetic rats. The results show that the leaf extract and fractions of S. anomalum has antioxidative stress and hepatoprotective potentials which may be due to the antioxidant activities of their phytochemical constituents.